Pengaruh Literasi Keuangan, Kompetensi, dan Penggunaan Sosial Media terhadap Kinerja UMKM - Inggrid Marisca Rubiyanty; Lulu Syifa Fadhila; Salma Putri Mellinia (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to determine the relationship between the influence of financial literacy, competence, and the use of social media on MSME performance. This study was conducted using a quantitative approach. Quantitative approach with survey method. The data analysis tool used is the SPSS 26.0 application. Data is processed by multiple linear regression analysis, classical assumption test, hypothesis testing. The sampling technique used was quota sampling. Data collection is done online by distributing Google Form. The questionnaire was distributed to 70 respondents. The results of the study can be interpreted that (1) financial literacy has a positive effect on MSME performance, (2) competence has a positive effect on MSME performance, and (3) the use of social media has a positive effect on MSME performance.